The Current of Disaster Medicine in Japan - Ohta, Muneo (Nihon Kyukyu Igakukai Zasshi, 2009)
Japan is a disaster-prone country, and has historically experienced many major disaster-related tragic incidents. Despite this, the importance of disaster preparedness had not been really recognized for many decades until the occurrence of the Hanshin-Awaji Earthquake in 1995 as a result of which more than 6000 lives were lost. In addition, starting from the 1990's, the type, nature and scale of disasters have changed very rapidly and globally. Japan also experienced some man-made disasters such as terrorism (the Sarin disaster), and nuclear accidents. Changes in the characteristics of disasters seriously stimulated Japanese medical professionals to design a modern medical disaster response system focused on disaster prevention, mitigation of victims, reducing preventable deaths and so on, because the very large gap between the actual status of modern medical technology and the medical response generated by the Hanshin earthquake was very clearly revealed. Therefore, many modern medical disaster systems have been designed from the onset of the New Millennium. The present study focuses on four articles on the current status of disaster medicine, according to the request to describe the substance of the author's special lecture made at the 36th Annual Meeting of the Japanese Association for Acute Medicine in 2008. These articles are; 1) The relationship between emergency medicine and disaster medicine; 2) Construction of a research organization on disaster medicine; 3) Activities of the Japanese Association for Disaster Medicine; and 4) Recent and future subjects of disaster medicine. The main point from each article can be summed up as follows: 1) The relationship between emergency medicine and disaster medicine must be close, however, the medical categories differ from each other. 2) Research structure has been organized under three main groups: the World Association for Disaster and Emergency Medicine, WADEM, founded in 1979; the Asian-Pacific Conference on Disaster Medicine, APCDM, founded in 1988; and the Japanese Association for Disaster Medicine, JADM, founded in 1996. 3) The JADM has more than 1000 members, has achieved miscellaneous and specialized activities, and is contributing to the development of disaster medicine not only in Japan but also in Asian countries. 4) Recent and future subjects are also miscellaneous and specialized such as education, rapid disaster response structure, and international assistance in the event of major international disasters as a humanitarian action. Finally, I'd like to emphasize my personal opinion and concludes that; “The maturity of a society can be evaluated by the investment for emergencies and-or disasters made by the society”.